Migration and International Relations IMISCOE Short Reader - Wihtol de Wenden, Catherine (IMISCOE Research Series, 2023)
This open access short reader investigates how migration has become an increasingly important issue in international relations since the turn of the 21st century. It investigates specific aspects of this migration diplomacy such as double citizenship or bilateral agreements on border controls which can become important tools for bargain or pressure. This short reader also discusses the intersections between migration and international relations concerning issues of global governance such as conflicts and refugees, development and mobility, or environmental migration. The book thereby shows the extent of bargaining involved in migration and international relations, the so called "soft diplomacy of migrations" as seen in the EU/Turkish agreement on borders in 2016, or the EU negotiations with Maghreb or Sub-Saharan countries on read missions against development programs and visas. As such this reader provides a must read to students, academics, researchers and policy makers and everyone who wants to learn more about the international relations aspects of migration governance.